PENGARUH STRUKTUR AUDIT, KOMITMEN ORGANISASI DAN EFEKTIVITAS PENGGUNAAN TEKNOLOGI SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA AUDITOR - Sihite, Elsa Sari; Sudarmadi (Jurnal Nusa Akuntansi, 2024)
This research aims to determine the influence of audit structure, organizational commitment, and the effectiveness of using accounting information system technology on auditor performance at the Tangerang public accounting firm. The type of research used in this research is quantitative research. The data source used in this research is primary data. The population in Tangerang is 2 Public Accountants with 33 auditors. Determining the sample in this study used the total sampling method because the total population was less than 100, so the entire population was used as a sample. The analysis technique uses multiple linear regression analysis, classic assumption tests consisting of normality tests, multicollinearity tests and heteroscedasticity tests. Hypothesis testing uses the coefficient of determination test, F test, and T test. Data analysis uses SPSS version 29 software. The results of this research show that audit structure, organizational commitment, and the effectiveness of using accounting information system technology influence auditor performance.